2002
DOI: 10.1046/j.1529-8027.2002.2008_9.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Investigation of Patients With Chronic Polyneuropathy: Evaluation of a Clinical Guideline

Abstract: Objective-(1) To evaluate a clinical guideline for the diagnostic investigation of patients presenting with signs and symptoms (present for longer than 6 weeks) suggesting a chronic polyneuropathy. (2) To investigate the contribution of electrophysiological studies to a focused search for aetiology in these patients. Methods-A chart review was carried out of a consecutive group of outpatients in 1993-7 at a university department of neurology, with signs and symptoms suggesting a polyneuropathy in whom the diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 7 publications
1
32
0
1
Order By: Relevance
“…In some patients, this was the only abnormal electrodiagnostic finding that reflected pathology in the sensory peripheral nervous system. As in previous studies, we also found that tibial motor velocity, 3,5 tibial F-wave latency, 1,2,7 H-reflex testing, 5,10 and needle EMG of distal foot muscles 9 were sensitive for detecting pathological changes.…”
Section: Discussionsupporting
confidence: 87%
“…In some patients, this was the only abnormal electrodiagnostic finding that reflected pathology in the sensory peripheral nervous system. As in previous studies, we also found that tibial motor velocity, 3,5 tibial F-wave latency, 1,2,7 H-reflex testing, 5,10 and needle EMG of distal foot muscles 9 were sensitive for detecting pathological changes.…”
Section: Discussionsupporting
confidence: 87%
“…A study of this strategy found half of neurophysiological studies performed added nothing to the eventual diagnosis in the investigation of patients with a distal symmetrical polyneuropathy of more than six weeks duration. 8 This study also reassuringly found that those patients with demyelinating neuropathies were recognised on clinical grounds.…”
Section: Peripheral Neuropathiesmentioning
confidence: 61%
“…2), что сви-детельствовало о выраженных проявлениях сенси-тивной атаксии. Таким образом, симптомы ПП ассоциированной с MGUS, весьма разнообразны и часто клинически схожи клиническими проявлениями с хронической воспалительной демиелинизирующей полиней-ропатией (ХВДП) [19,20]. Реже встречаются аксо-нальный тип поражения периферических нервов, тонких немиелинизированных волокон и синдром множественной несимметричной мононевропатии.…”
Section: результаты и обсуждениеunclassified